Differential Effects of Inoculation with Earthworms and Phosphate-Solubilizing Bacteria on Phosphorus Adsorption Capacity of Soils with Different Phosphorus Contents - Feiyu Dong; Leixin Yu; Yimeng Jiao; Tianqi Wang; Qinghai Yang; Chuang Yang; Lijuan Yang (Agronomy)
Due to the strong fixation and weak mobility of phosphorus (P) in the soil, P fertilizers can easily be left behind in the soil, which greatly increases the environmental pressure. To find a green and environmentally friendly method of P activation, this study evaluated the effects of inoculation with earthworms and phosphate-solubilizing bacteria (PSB) on the adsorption and desorption in low-phosphorus (LP) and high-phosphorus (HP) soils substrates. In LP soils, inoculation with earthworms or (and) PSB reduced the maximum P adsorption, P adsorption affinity constant and maximum buffering capacity by 3–12%, 7–19% and 10–28%, respectively, while the readily desorbed P, degree of P saturation and desorption rates were significantly higher in the inoculated treatments. In HP soils, treatments inoculated with earthworms significantly increased the P adsorption affinity constants (16–22%) and maximum buffer capacity (8–16%) and decreased the adsorption saturation and desorption rates compared to no inoculum. The results indicate that inoculation with earthworms or (and) PSB can effectively reduce the P adsorption capacity and increase the P desorption capacity of LP soils, thus increasing the available P content. However, in HP soils, inoculation with earthworms increased the P adsorption capacity and reduced the risk of P losses due to high-P soil content.